Vaping, smartphones, and social media use among young adults: Snapchat is the platform of choice for young adult vapers. (January 2021) - Massey, Zachary B.; Brockenberry, Laurel O.; Harrell, Paul T.
Highlights: Higher frequency of social media use was associated with higher rates of vaping. The most commonly used platforms were Snapchat, Instagram, YouTube, and Facebook. Ever-vapers used more social media platforms than never-vapers. Snapchat and Instagram use were associated with vaping ad exposure via smartphones. However, only Snapchat use was associated with higher rates of vaping. Abstract: Background: Tobacco use often begins or stabilizes in young adulthood. Approximately 90% of young adults use social media and over 80% own a smartphone. Retailers of electronic nicotine delivery systems (ENDS) have targeted smartphones and social media with adverting campaigns. Despite evidence of ENDS advertising on social media and smartphones, few studies have examined associations between exposure to vaping advertisements on smartphones, social media use, and ENDS use (i.e., vaping) among young adults. Methods: College students aged 18–24 from a large public university ( N  = 1047) completed online surveys about vaping. The survey measured frequency of vaping advertisement exposure, smartphone use, social media use, and vaping behaviors. Hierarchical logistic regression assessed whether demographics, vaping advertisement exposure, smartphone use, and social media use predicted ever vaping compared to never vaping. Results: The four most commonly used platforms (used "daily") were Snapchat (80.0%), Instagram (73.4%), YouTube (59.7%), and Facebook (54.3%). Use of Snapchat, Instagram, and Facebook were all significantly associated with higher rates of vaping advertisement exposure via smartphones. Exposure to vaping advertisements on smartphones was associated with ever vaping (AOR: 1.30, 95% CI = 1.05–1.60). Of the social media platforms examined, only Snapchat use frequency was associated with higher odds of ever vaping (AOR: 1.22, 95% CI = 1.10–1.36). Conclusions: Exposure to advertisements via smartphones and use of Snapchat were associated with higher rates of vaping for young adults. Social media and smartphone use should be further investigated for young adult impact.